Spatial Character as a Mediator of Social Interaction in Sibuhuan Traditional Market: A Phenomenological Study - Hafidzah Sulastri; Vinky Rahman; S. Wahyuni Zahrah (Universitas Medan Area, 2026)
Traditional markets function not only as economic spaces but also as social environments whose meanings are continuously shaped through users’ everyday experiences. This study aims to examine how the spatial character of Sibuhuan Traditional Market mediates social interaction and contributes to users’ spatial meanings. A qualitative phenomenological approach was employed to explore the lived experiences of traders, buyers, and market managers. Data were collected through field observations, semi-structured interviews, and documentation and analyzed through phenomenological coding, meaning-unit identification, thematic categorization, and interpretation of experiential patterns. The findings reveal five interconnected themes: spatial density as a collective experience, the subjective and contextual meaning of strategic locations, fluid boundaries between formal and informal spaces, social relationships as a determinant of spatial meaning, and the market as a lived space beyond its economic function. Repeated social interactions generate familiarity, place attachment, collective memory, and perceptions of strategic, comfortable, and valuable spaces. The study concludes that spatial character and social interaction have a reciprocal relationship, in which spatial configuration facilitates encounters while repeated interactions continuously reproduce the meaning of market space. The findings highlight the importance of considering social experience and place attachment in the planning and management of traditional markets.